Antimicrobial properties from different parts of Ficus Deltoidea / Norintan Sahali - Sahali, Norintan (2015)
Antimicrobial agents from natural sources gained attention as antimicrobial resistance has become a growing issue. Ficus deltoidea is a traditional medicine plant that clinically proven has antimicrobial properties. However, determination of antimicrobial properties from different parts ofFicus deltoidea is needed, as it able to identify the part of the plant that possessed antibacterial properties against Staphylococcus aureus (ATCC 43300), Bacillus cereus (ATCC 14579), Escherichia coli (ATCC 25922), and Pseudomonas aeruginosa (ATCC 27853). Screening of antimicrobial activity of methamlic extract of the lea~ stem, fig, and root ofFicus deltoidea was made using disc diffusion method, followed by minimum inhibition concentration (MIC) and minimum bactericidal concentration (MBC) for sensitive organisms. The preliminary screening showed inhibition activity of all Ficus deltoidea parts against Staphylococcus aureus and Bacillus cereus, but negative results for Escherichia coli and Pseudomonas aerugin0 sa. The MIC ofthe leafwas considered as good against Staphylococcus aureus and Bacillus cereus, same as the fig and stem against Staphylococcus aureus. While the remaining plant parts were considered as rmderate. The MBC test confirming bactericidal effects of all parts of Ficus deltoidea against both Staphylococcus aureus and Bacillus cereus. The leaf, stem, fig and root ofFicus deltoidea against Staphylococcus aureus has MBC value of62.5mg/ml, 125mglml, 125mg/ml and 250mg/ml. While against Bacillus cereus have a value of62.5mg/ml, 250mg/ml, 500mg/ml and 500mg/ml. This study reveals that Ficus deltoidea leaf, fig, stem and root extract have antibacterial activities against Staphylococcus aureus and Bacillus cereus, and could potentially be used as a natural antibacterial agent to treat bacterial infections.